Efektifitas pendidikan kesehatan menggunakan media audiovisual terhadap perilaku Pencegahan filariasis - Satri Mayu Santi; Febriana - Sabrian; Darwin - Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the effectiveness of health education using audiovisual media to improve filariasis prevention behavior. This was quasi experiment study with implementation of health education using audiovisual media. This research was conducted in Kelurahan Sungai Apit, Desa Mengkapan, Desa Teluk Batil, Desa Harapan, Kecamatan Sungai Apit Kabupaten Siak with 32 respondents. Researcher used questionnaire instrument about knowledge, attitude, action, and observation sheet, which was developed by researcher. The data were analyzed by univariate and bivariate analysis with dependent t-test. The result showed a health education using audiovisual media was effective for filariasis prevention behavior with p value < α (0,00 < 0,05). Based on the result of this study, health provider’s in Puskesmas are recommended to apply this methods to improve community behavior for preventing filariasis disease. Keyword: Audiovisual, filariasis, health education, prevention behavior